Coalition-based Routing and Resource Optimisation Method for 5G User Communications - S. Pragadeswaran; B. Nataraj (Elektronika ir Elektrotechnika)
The fifth generation (5G) technology provides high transmission and low latency communication to users by integrating heterogeneous devices and maximum radio resource utilisation. Prolonged longevity and effective communication are achieved through active resource routing. In addition, interference-less routing and lossless resource allocation are essential for ensuring successful communication. The transmitting and receiving users rely on shared channels to maximise resource utilisation where interference has a significant issue. In this article, a coalition-based routing and resource optimisation (CRRO) method is proposed to improve the performance of 5G communications. The proposed method relies on the cooperative agreement between resource providers and allocation channels to distinguish the sharing intervals. Maximum routing conditions for devices, service providers, and user routing are met with high longevity. In the coalition-based resource selection, synchronisation between the communicating is considered to maximum interference-less routing efficiency. A modified deep transfer learning is included in the interference level verification based on longevity and low interference to verify the synchronised behaviour of the routing process. The proposed method significantly improves the performance of 5G networks. By dynamically optimising resource allocation, minimising interference, and extending the longevity of the routing, it adapts resource utilisation to the varying conditions of the network and the demands of the users. The proposed CRRO improves resource utilisation and routing longevity by 10.02 %, and 14.41 %, respectively, and reduces latency by 10.47 % for the maximum interval.